Prevalence of and Associated Factors for Overactive Bladder Subtypes in Middle-Aged Women: A Cross-Sectional Study - Cheng-Fang Yang; Chao-Yuan Huang; Shu-Yi Wang; Shiow-Ru Chang (Medicina, 2022)
Background and Objectives: The living environment can manifest physiological responses in humans, with cohabiting couples often having similar health statuses. The aim of this study was to (1) examine the prevalence of the overactive bladder (OAB) with or without incontinence and (2) identify associated factors for OAB with and without incontinence (including environmental factors, such as living with a partner who has OAB) in middle-aged women. Materials and Methods: In this cross-sectional study, the International Consultation on Incontinence Questionnaire Overactive Bladder (ICIQ-OBA) was administered to 970 couples. Data were analyzed using descriptive statistics, chi-square analyses, and multivariate logistic regression. Results: Responses to the ICIQ-OBA among middle-aged women generated a higher prevalence of OAB with incontinence (OABwet; 41%) than OAB without incontinence (OABdry; 26%; p < 0.001). The factors associated with OABwet were as follows: being age ≥ 55 years (odds ratio [OR], 1.41; 95% confidence interval [CI], 1.02–1.95), having a body mass index (BMI) ≥ 27 kg/m2 (OR, 1.50; 95% CI, 1.03–2.17), having vaginitis (OR, 1.89; 95% CI, 1.28–2.80), and having partners with OABwet (OR, 2.35; 95% CI, 1.74–3.19). Having partners with OABdry (OR, 1.81; 95% CI, 1.34–2.44) was an associated factor for OABdry. Conclusions: This study identified the associated factors for OAB subtypes (OABwet and OABdry) in middle-aged women. These findings can support treatment and preventive strategies for health providers who care for patients with OAB. As part of the treatment and preventative strategies, the risk that partners may introduce to the development of OAB in women should also be considered.